2013
DOI: 10.1038/pr.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism associations with preterm delivery: a case–control replication study and meta-analysis

Abstract: Background:The aim of this study was to replicate singlenucleotide polymorphism (SNP) associations with preterm birth (PTB; birth at <37 completed weeks of gestation) and synthesize currently available evidence using meta-analysis. Methods: Spontaneous PTB cases and controls were selected from an existing cohort. Candidate SNPs were taken from an existing genotype panel. A systematic review was conducted for each SNP in the panel to determine suitability as a PTB candidate. Those with significant associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Many of the associations reported to date lack replication, and there is substantial variation between reports, including mixed ethnicities, variable cohort sizes, differing genetic models applied and different definitions of preterm birth between studies. One recent case-control replication study found only factor V Leiden to be significantly associated with preterm birth, and meta-analysis confirmed its association (O'Callaghan et al 2013). These authors found that 980 papers had been published on SNPs and preterm birth, reviewed 78 of these and came up with eight SNPs to test as replication candidates.…”
Section: Preterm Birthmentioning
confidence: 96%
See 1 more Smart Citation
“…Many of the associations reported to date lack replication, and there is substantial variation between reports, including mixed ethnicities, variable cohort sizes, differing genetic models applied and different definitions of preterm birth between studies. One recent case-control replication study found only factor V Leiden to be significantly associated with preterm birth, and meta-analysis confirmed its association (O'Callaghan et al 2013). These authors found that 980 papers had been published on SNPs and preterm birth, reviewed 78 of these and came up with eight SNPs to test as replication candidates.…”
Section: Preterm Birthmentioning
confidence: 96%
“…One recent case–control replication study found only factor V Leiden to be significantly associated with preterm birth, and meta‐analysis confirmed its association (O'Callaghan et al . ). These authors found that 980 papers had been published on SNPs and preterm birth, reviewed 78 of these and came up with eight SNPs to test as replication candidates.…”
Section: Introductionmentioning
confidence: 97%